Stereotypowe postrzeganie polityków - Dolińska-Zygmunt, Grażyna; Jarco, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
In May 2003 we conducted the poll research on the perception of Polish politicians by Polish people. The aim of the survey was to examine a stereotype profile of Polish politician. The research was made on the group of 200 respondents. The stereotype of Polish politician is deeply pejorative. A politician is associated with governing class. There is traditionally-based aversion towards government in Poland. It is blamed for bad intentions and called as "Others". (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 167-181